POWER PEREMPUAN DALAM TRADISI MUSIK BECANANG DI BENER MERIAH - Rika Wirandi; Fifie Febryanti Sukman (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2022)
This study aims to identify and examine the existence and role of women in the bronze musical tradition: becanang in Bener Meriah. The extent of the role of men in Aceh, including various forms of performing arts activities known as Islamic – the becanang music culture has survived for a long time until now with supporters and performers of the culture being women. The importance of this research to be carried out for several reasons and considering the lack of studies on traditional music from a gender perspective to date in Indonesia, especially in Aceh. In addition, the reason for the low interest of traditional music researchers to conduct studies on the presence of women in Indonesian music culture from a gender perspective. This research uses descriptive qualitative research methods using several data collection techniques, including: literature studies and static archives, direct observation, interviews with sources from various backgrounds, documenting object events contextually, to the selection stage to field data analysis. The gender perspective is an analytical perspective that will later be used to look at gender issues in becanang music culture and the role and existence of women in the life of this musical tradition. This study concludes that, becanang can be regarded as entertainment music and music to encourage work whose musical traditions are brought to life by women. All types of traditional music that use canang musical instruments (bronze and bamboo) as well as arts that use the term